Respuesta :
Answer:
-9
Step-by-step explanation:
We are given the value of "a", which is 6. Let us substitute the value of "a" into the expression to determine a numerical value of 3(a - 9).
- ⇒ 3(a - 9)
- ⇒ 3[(6) - 9] . . . . . . . . {a = 6}
Open the parentheses to simplify the expression inside the long brackets [ ].
- ⇒ 3[(6) - 9] . . . . . . . . {a = 6}
- ⇒ 3[6 - 9]
Subtract the expression inside the long brackets [ ]
- ⇒ 3[6 - 9]
- ⇒ 3[-3]
Finally, simplify the product of 3 and -3.
- ⇒ 3[-3]
- ⇒ 3 × -3 = -9
Therefore, -9 is the value of 3(a - 9) when a = 6.
Learn more about this topic: https://brainly.com/question/12060168
[tex]\huge\text{Hey there!}[/tex]
[tex]\mathsf{3(a - 9)}\\\\\mathsf{= 3(\bold{6} - 9)}\\\\\mathsf{= 3(6) + 3(-9)}\\\\\mathsf{= 18 - 27}\\\\\large\text{OR EVEN \rm{3(-3)}}\\\\\mathsf{= 3(-3)}\\\\\mathsf{= -9}\\\\\\\\\huge\text{Therefore, the answer is: \boxed{\mathsf{-9}}}\huge\checkmark[/tex]
[tex]\huge\text{Good luck on your assignment \& enjoy your day!}[/tex]
~[tex]\frak{Amphitrite1040:)}[/tex]